Academic stress and sleep quality as a predictor towards eating behaviour among university students - Sahid, Noor Isyah Amira; Ibrahim, Muhamad Ariff; Saad, Nurulwahida; Mohd Nazori, Mohd Nazir; Lokman, Muhammad Hazim; Shamsuddin, Aida Soraya (IIUM Press, 2023)
Introduction: Academic stress has been identified to be the main stressor, particularly among university students which cause negative effects on health as well as academic performance. University students also experience poor sleep quality. This study is conducted to identify the level of academic stress, sleep quality and eating behaviour, the relationship between academic stress, sleep quality and eating behaviour as well as to investigate the influence of academic stress and sleep quality towards eating behaviour among IIUM students. Methods: A cross – sectional study was conducted using convenience sampling, with a total sample of 410 students. Data were collected using the Educational Stress Scale for Adolescents (ESSA), Sleep Quality Scale (SQS) and Dutch Eating Behaviour Questionnaire (DEBQ). Results: The study reported that 46.3% of the students experienced low academic stress. Furthermore, there is a significant association between academic stress with restrained (r=0.245), emotional (r=0.224) and external eating behaviour (r=0.180). There were 75.6% of students reported having no sleep problem. There is a significant association between sleep quality with restrained (r= 0.162), emotional (r=0,260) and external eating behaviour (r=0.184). In addition, the result from regression analysis for academic stress and sleep quality towards restrained eating behaviour explained only 7.1% variance. Similarly the percentage of variance explained for emotional behaviour was 9.4% and external eating behaviour was just 5.3%. Thus, emotional eating behaviour is the most significant compared to other associations. Conclusion: This finding can be helpful in increasing the awareness of the students towards healthy lifestyle and provide a good intervention to manage academic stress as well sleep problem.